TINJAUAN NORMATIF PERAN DEWAN KEAMANAN PERSERIKATAN BANGSA-BANGSA (PBB) DALAM MENJAGA PERDAMAIAN DUNIA (Studi kasus KONFLIK ANTARA RUSIA DAN UKRAINA) - Dewi Aisyah; Arlina Permanasari (Fakultas Hukum Universitas Trisakti, 2021)
The attack of the Russian Federation is a flagrant violation of the Charter of the United Nationsand international law. In carrying out the obligations of the UN Security Council as stated in theCharter of the United Nations (UN), the Security Council has made efforts to deal with the conflictbetween Russia and Ukraine by issuing Resolutions to maintain world peace and security. In theresults of the Resolution issued by the United Nations, it did not produce any results, the reasonwas that Russia had a veto power over the resolution. The purpose of writing is to find out andanalyze the causes and impacts of the conflict between Russia and Ukraine on various countries,the role of the Security Council and the General Assembly. This research method is using theliterature study method used by the author with the aim of obtaining complete and accountabledata through books, literatures, notes, and existing reports.